2022
DOI: 10.5194/bg-19-1321-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peatland management on aquatic carbon concentrations and fluxes

Abstract: Abstract. Direct land-to-atmosphere carbon exchange has been the primary focus in previous studies of peatland disturbance and subsequent restoration. However, loss of carbon via the fluvial pathway is a significant term in peatland carbon budgets and requires consideration to assess the overall impact of restoration measures. This study aimed to determine the effect of peatland land management regime on aquatic carbon concentrations and fluxes in an area within the UK's largest tract of blanket bog, the Flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…More recent work at multiple (20) sites on Eaglesham Moorland recorded [DOC] ranging from 6.1 to 137.0 mg L −1 (Heal et al 2020). DOC concentrations at Drumtree were higher than drained, nondrained, and restored peatlands in far‐north Scotland, which ranged from 3.8 mg L −1 (nondrained) to 42.2 mg L −1 (drained) (Pickard et al 2022). The nondrained sites, likely to reflect the peat status most closely at Drumtree, had lower TOC export (7.9–9.2 g C m −2 yr −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent work at multiple (20) sites on Eaglesham Moorland recorded [DOC] ranging from 6.1 to 137.0 mg L −1 (Heal et al 2020). DOC concentrations at Drumtree were higher than drained, nondrained, and restored peatlands in far‐north Scotland, which ranged from 3.8 mg L −1 (nondrained) to 42.2 mg L −1 (drained) (Pickard et al 2022). The nondrained sites, likely to reflect the peat status most closely at Drumtree, had lower TOC export (7.9–9.2 g C m −2 yr −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 11 studies reviewed showed a mean 8 % increase in DOM concentrations following ditch blocking, although this figure is skewed by the large increases reported by Worrall et al (2007b) and Haapalehto et al (2014) (100 % increase immediately following ditch blocking and 50 %-75 % increases after 10 and 5 years, respectively); the median change is zero. Importantly, no significant change in DOM concentration was reported in over half of these studies (O'Brien et al, 2008;Gibson et al, 2009;Armstrong et al, 2010;Wilson et al, 2011;Evans et al, 2018;Pickard et al, 2022). Likewise, a recent study found no reduction in DOM concentrations at a restored site compared to a ditched site 6 years after ditch blocking, while both the drained and restored site DOM concentrations remained elevated compared with the non-drained control (Pickard et al, 2022).…”
Section: Ditch Blockingmentioning
confidence: 91%
“…Importantly, no significant change in DOM concentration was reported in over half of these studies (O'Brien et al, 2008;Gibson et al, 2009;Armstrong et al, 2010;Wilson et al, 2011;Evans et al, 2018;Pickard et al, 2022). Likewise, a recent study found no reduction in DOM concentrations at a restored site compared to a ditched site 6 years after ditch blocking, while both the drained and restored site DOM concentrations remained elevated compared with the non-drained control (Pickard et al, 2022). Differences between studies with respect to the apparent effect size may in part be related to the experimental design, including whether the work included a simultaneous control, and the time period over which post-restoration monitoring was carried out.…”
Section: Ditch Blockingmentioning
confidence: 95%
See 1 more Smart Citation
“…The potential effects on water-related ecosystem services are intrinsically linked (Flynn et al, 2021 ; Pschenyckyj et al, 2021 ), with the relationship between peatlands and water quality being internationally recognised (Rothwell et al, 2010 ; Nieminen et al, 2021 ; Williamson et al, 2021 ; Pickard et al, 2022 ). According to the latest Water Quality in Ireland report, just over half of surface water bodies in the country meet satisfactory water quality levels, with quality continuing to decline (O’Boyle et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%